Cisplatin causes erectile dysfunction by decreasing endothelial and smooth muscle content and inducing cavernosal nerve senescence in rats - Yin, Yinghao; Zhou, Yihong; Zhou, Jun; Zhao, Liangyu; Hu, Hongji; Xiao, Ming; Niu, Bin; Peng, Jingxuan; Dai, Yingbo; Tang, Yuxin (Frontiers in Endocrinology, 2023)
Cisplatin (cis‐diamminedichloroplatinum II, CDDP), a drug widely used for cancer worldwide, may affect erectile function, but its side effects have not received enough attention. To investigate the effect of CDDP on erectile function and its possible mechanism. Sprague−Dawley rats were intraperitoneally administered CDDP (CDDP group) or the same volume of normal saline (control group). Erectile function was evaluated after a one-week washout. Then, histologic changes in the corpus cavernosum and cavernous nerve (CN) were measured. Other Sprague-Dawley rats were used to isolate the major pelvic ganglion and cavernous nerve (MPG/CN). RSC96 cells were then treated with CDDP. SA-β-gal staining was used to identify senescent cells, and qPCR was used to detect the senescence-associated secretory phenotype (SASP). Finally, the supernatant of RSC96 cells was used to culture MPG/CN. Erectile function was measured after administration of CDDP. The cavernosum levels of α-SMA, CD31, eNOS, and γ-H2AX, the apoptosis rate and the expression of p16, p21 and p53 in CN were also assayed. The senescent phenotype of RSC96 cells treated with CDDP was identified, and neurite growth from the MPG/CN was photographed and measured. The CDDP group had a significantly lower ICP/MAP ratio than the control group. Compared to the control group, the CDDP group exhibited significantly lower α-SMA, CD31 and eNOS levels and significantly higher γ-H2AX and apoptosis rates in corpus cavernosum. In addition, CDDP increased some senescence markers p16, p21 and p53 in CN. In vitro, CDDP induced RSC96 senescence and SASP, and the supernatant of senescent cells slowed neurite outgrowth of MPG/CN. In conclusion, CDDP treatment could induce erectile dysfunction, by affecting the content of endothelial and smooth muscle and causing SASP in CN. The results indicate that CDDP treatment should be considered as a risk factor for ED. Clinicians should pay more attention to the erectile function of cancer patients who receive CDDP treatment.